2015
DOI: 10.1037/cou0000083
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of an acceptance and commitment therapy adjunctive web-based program for counseling centers.

Abstract: Web-based adjunctive tools provide a promising method for addressing the challenges college counseling centers face in meeting the mental health needs of students. The current study tested an initial adjunctive prototype based on acceptance and commitment therapy (ACT) in a pre-post open trial with 30 counselors and 82 student clients across 4 counseling centers. Results indicated high ratings of program satisfaction and usability with counselors and students. The majority of students completed at least part o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
63
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 44 publications
(70 citation statements)
references
References 18 publications
6
63
0
1
Order By: Relevance
“…Such strategies could be implemented from a supportive accountability approach in which a professional or paraprofessional provides ongoing guidance and support for students using the program, which is an effective and standard way intervention developers have typically improved program engagement and adherence (Mohr, Cuijpers, & Lehman, ). Consistent with this, initial research suggests ACT‐CL could be effective, at least for more acute treatment, in an adjunctive guided self‐help format with counselors providing guidance (Levin et al., ). Thus, ACT‐CL might be improved in part by adjusting how the program is implemented, such as providing more supportive accountability to users.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Such strategies could be implemented from a supportive accountability approach in which a professional or paraprofessional provides ongoing guidance and support for students using the program, which is an effective and standard way intervention developers have typically improved program engagement and adherence (Mohr, Cuijpers, & Lehman, ). Consistent with this, initial research suggests ACT‐CL could be effective, at least for more acute treatment, in an adjunctive guided self‐help format with counselors providing guidance (Levin et al., ). Thus, ACT‐CL might be improved in part by adjusting how the program is implemented, such as providing more supportive accountability to users.…”
Section: Discussionmentioning
confidence: 86%
“…Several recent randomized trials have demonstrated the efficacy of web‐based self‐help ACT for depression (e.g., Lappalainen et al., ), chronic pain (e.g., Trompetter et al., ), smoking (e.g., Bricker, Wyszynski, Comstock, & Heffner, ), and tinnitus (e.g., Hesser et al., ). Research specifically with university students has found that ACT in a web‐based self‐help format can improve academic performance (Chase et al., ) and psychological symptoms as an adjunct to counseling services (Levin, Pistorello, Hayes, Seeley, & Levin, ). Overall, this research suggests ACT may be feasible as a prevention approach and in a web‐based self‐help format, although only one study has specifically tested ACT as a transdiagnostic web‐based self‐help prevention program (Levin, Pistorello, Hayes, & Seeley, ).…”
mentioning
confidence: 99%
“…When ACT‐CL was used as an adjunctive with face‐to‐face counseling, Levin et al. () reported lower completion rates of 67% (module 1), 49% (module 2), and 38% (module 3), and a postintervention assessment completion rate of 44%. Finally, Rasanen et al.…”
Section: Discussionmentioning
confidence: 99%
“…The ACT‐CL group ( n = 37) evidenced greater improvements on education values and motivation, and depression compared to a waitlist group ( n = 39). In a subsequent pre‐ and postintervention open trial study, Levin, Pistorello, Hayes, Seeley, and Levin () updated ACT‐CL from two to three online sessions targeting the ACT processes values, acceptance and mindfulness, and added four training sessions for counselors ( n = 30) so the program could be offered as an optional counseling adjunctive for students already receiving face‐to‐face treatment ( n = 82) with counselors in university counseling centers. Most participants improved on depression, anxiety, stress, psychological flexibility, mindfulness, and education values.…”
Section: Introductionmentioning
confidence: 99%
“…The PVQ‐II was derived from the well‐validated and widely used measure of personal strivings developed by Emmons (; ) and expanded by Sheldon and colleagues (). Although the domain assessed in the current study has not been previously validated and used on its own in published research, other studies have adapted the PVQ‐II to focus on one or more specific domains (e.g., Ferssizidis et al., ; Levin, Hayes, Pistorello, & Seeley, ; Levin, Pistorello, Hayes, Seeley, & Levin, ).…”
Section: Methodsmentioning
confidence: 99%